(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
Main objective’s research was to determine the impact of reverse marketing in its dimensions (reverse product, reverse pricing, reverse distribution, reverse promotion) on the purchasing decision of consumers of single-use plastic bags in Syrian markets. The researcher analysed (385) questionnaires distributed to a random sample of consumers of plastic bags using the statistical analysis program (SPSS-28). The researcher concluded that there is a statistically significant effect for all dimensions of reverse marketing, on the purchasing decisions of consumers of single-use plastic bags.The most important recommendations were: ensuring the use of reverse marketing to reduce the use of plastic bags within an integrated social, cultural, and economic strategy, to achieve the desired effectiveness, ensuring the sustainable involvement of various civil society organizations to achieve reverse marketing objectives, and avoiding adopting uniform reverse marketing policies across all regions, as each region has its cultural characteristics, consumer behaviour, and influential demographic factors.